Acute Vertebral Artery Origin Occlusion Leading to Basilar Artery Thrombosis Successfully Treated by Angioplasty with Stenting and Thrombectomy. Issue 3 (May 2014) - Abe, Arata; Okubo, Seiji; Onozawa, Shiro; Nakajima, Masataka; Suzuki, Kentaro; Harada-Abe, Mina; Ueda, Masayuki; Katsura, Ken-Ichiro; Katayama, Yasuo
Few reports have described the successful treatment of stroke caused by acute vertebral artery (VA) origin occlusion by endovascular surgery. We describe the case of a 68-year-old man who experienced stroke due to left acute VA origin occlusion. Cerebral angiography showed that the left VA was occluded at its origin, the right VA had hypoplastic and origin stenosis, and the basilar artery was occluded by a thrombus. The VA origin occlusion was initially passed through with a 0.035-inch guide wire. An angioplasty was performed, and a coronary stent was appropriately placed. The VA origin was successfully recanalized. A balloon-assisted guiding catheter was navigated through the stent and a thrombectomy was performed using the Penumbra system. The patient's symptoms gradually improved postoperatively. Balloon-assisted catheter guidance through a vertebral artery stent permitted a successful thrombectomy using the Penumbra system and may be useful for treating stroke due to VA origin occlusion.